See and spy counting - Aigner-Clark, Julie; Zaidi, Nadeem (New York : Hyperion Books for Children, 2001)
Bright pictures and simple text teach young readers to count to five.
"Ages 9 mos. and up"--Cover p. [4].
Cover title.
On board pages.
2.1
K-3
Keywords: Counting -- Juvenile literature; Counting; Counting